2019
DOI: 10.1302/0301-620x.101b6.bjj-2018-1448.r1
|View full text |Cite
|
Sign up to set email alerts
|

Can some early revision total hip arthroplasties be avoided?

Abstract: Aims Studying the indications for revision total hip arthroplasty (THA) may enable surgeons to change their practice during the initial procedure, thereby reducing the need for revision surgery. The aim of this study was to identify and describe the potentially avoidable indications for revision THA within five years of the initial procedure. Patients and Methods A retrospective review of 117 patients (73 women, 44 men; mean age 61.5 years (27 to 88)) who met the inclusion criteria was conducted. Three adult r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“… 2–4 Specifically, malpositioning of the acetabular cup has been associated with adverse outcomes, with the consequences including reduced range of motion, 5–7 increased risk of dislocation, 8 , 9 increased component wear, 10 increased impingement, 5 , 6 increased pain, and a resultant higher rate of revision. 11 In fact, it has been suggested that 48% of avoidable revision THAs were the result of malpositioning of the acetabular cup. 11 Improving acetabular cup orientation may, therefore, reduce adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2–4 Specifically, malpositioning of the acetabular cup has been associated with adverse outcomes, with the consequences including reduced range of motion, 5–7 increased risk of dislocation, 8 , 9 increased component wear, 10 increased impingement, 5 , 6 increased pain, and a resultant higher rate of revision. 11 In fact, it has been suggested that 48% of avoidable revision THAs were the result of malpositioning of the acetabular cup. 11 Improving acetabular cup orientation may, therefore, reduce adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“… 11 In fact, it has been suggested that 48% of avoidable revision THAs were the result of malpositioning of the acetabular cup. 11 Improving acetabular cup orientation may, therefore, reduce adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This methodology was adapted from a 2019 study by Novikov et al. looking at potentially avoidable causes of rTHA [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Avoidable revisions indications are defined as those that result from an insufficiency of care by the medical provider as determined by the provider’s peers [ 13 ]. Potential avoidable indications for revision have been investigated in total hip arthroplasty (THA), but from our literature review, no studies have been published looking at potential avoidable indications for rTKA [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years there have been a significant advance in prosthesis design ranging from the shape, coating and modality of fixation [2]. However, post-operative complications due to mechanical failure of implants still occur and component loosening is considered as one of the most common failure modes in cementless THA [3][4][5]. Although the risk of femoral loosening can be minimised by optimal component positioning, other factors such as patient age, weight, gender, osteopenia, stem design and Dorr-C bone have all been proposed as risk factors for poor fixation and subsequent stem subsidence and poor outcome [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%